Integrating Mrs. Ruswo's Leadership Values into History Learning through a Contextual Approach - Nurul Ismi Lestari; Dyah Kumalasari; Arfaton Arfaton; Mhd Asrian Syah; Muhamad Abdu (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the leadership values of Mrs. Ruswo, a key figure in the March 1, 1949, General Offensive during Indonesia’s struggle for independence. It aims to examine how her leadership can be integrated into contextual history learning to support character education, particularly in developing students’ leadership qualities. Employing a qualitative descriptive-analytical approach, data were gathered through literature review, semi-structured interviews with historians and educators, and field observations at relevant historical sites. The study focused on extracting leadership traits exemplified by Mrs. Ruswo and their pedagogical applications in secondary education. Findings reveal that Mrs. Ruswo demonstrated exceptional leadership through community mobilization, logistical support, and women's empowerment during the independence struggle. Her core leadership values include courage, social care, perseverance, vision, and empowerment. These values are aligned with the goals of character education and can serve as practical models in history teaching. Integrating Mrs. Ruswo’s leadership into history education through a contextual approach—such as reflective discussions, leadership projects, and field-based learning—enables students to relate historical content to real-life leadership challenges. This method fosters deeper engagement, critical thinking, and personal development. Educational implications highlight that incorporating local female figures like Mrs. Ruswo in curriculum design not only enriches historical understanding but also promotes inclusive and value-based education.